The Influence of Celebrity Endorser on Purchase Intention with Perceived Quality as Mediating Variable - Tharissa Kesturi; Rd. Nurafni Rubiyanti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The cosmetics industry is projected to continue to experience growth by the Indonesian Cosmetics Companies Association by 15% to Rp. 11.22 trillion from Rp. 9.76 trillion in 2012. One of the cosmetic brands in Indonesia is Wardah Cosmetic. The purpose of this study was to determine the effect of celebrity endorsers and Wardah Cosmetic's perceived quality on the buying interest. The method used in this research is the quantitative method, with the type of descriptive-causal analysis. Sampling with a non-probability sampling method with purposive sampling type with a sample size of 100 female consumers in the city of Bandung. The data analysis technique used is descriptive analysis technique and Partial Least Square - Structural Equation Model analysis. Based on SEM-PLS analysis, the celebrity endorser variable has a strong effect on purchase intention with a T-Statistics value of 7.486. Based on the moderation effect analysis, perceived quality perfectly mediates with a T-Statistics value of 1.124. The conclusion of this study, the variable perceived quality effectively influences as a perfect mediator towards celebrity endorsers and buying interest, which means that Wardah Cosmetic's use of celebrity endorsers is appropriate to affect the perceived quality of Wardah Cosmetic products and stimulate consumer buying interest.